CHANGING THE BEHAVIOR OF PLWHA AND OHIDA THROUGH DAKWAH COMMUNICATION SIMPLE BEHAVIOR OF PROPHETS AND APOSTLES AMID THE HEDONISM LIFESTYLE - Susdarwono, Endro Tri (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2023)
Da'wah communication is communication whose elements are adapted to the vision and mission of da'wah. This research aims to describe changes in the behavior of PLHAs and Ohida through communication, preaching the simple behavior of prophets and apostles amidst a hedonistic lifestyle. In this research, the approach used is a combination of qualitative and quantitative. This research concludes that the communication of preaching the simple behavior of the Prophet and Apostles was able to make changes to the simple behavior of PLHIV and Ohida amidst society's hedonistic lifestyle. This conclusion was obtained from statistical testing which stated that from this research (1) the communication of preaching the simple behavior of the Prophet and Apostle could create changes in the behavior of PLHIV and Ohida in the midst of society's hedonistic lifestyle, (2) there was a change in the behavior of PLHA and Ohida in carrying out simple behavior. according to the Prophet and Apostle in the midst of society's hedonistic lifestyle after da'wah communication.